Penambahan Kromium Organik pada Pakan Yang Dibatasi Terhadap Performa Produksi Puyuh - Ujang Suryadi; Budi Prasetyo; Jefri Bagus Santoso (Politeknik Negeri Jember, 2018)
The aim of this research was to know the effect of organic chromium on feed which was limited to quail phase pre-layer production performance. The experimental design of the study was a Completely Randomized Design (CRD) consisting of twelve treatments, three replicates, and each replication consisted of five quails. Data were analyzed by variance analysis then tested continued with the Least Significance Different (LSD). The treatments were P0R1 (adlibitum feed, energy metabolism (EM) 2,900 kcal/kg, protein 22%), P0R2 (adlibitum feed, EM 2,800 kcal/kg, 23% protein), P1R1 (restriction feed 10% of adlibitum, EM 2,900 kcal/kg, 22% protein), P1R2 (restriction feed 10% of adlibitum, EM 2,800 kcal/kg, 23%.protein), P2R1 (restriction feed 20% of adlibitum, EM 2,900 kcal/kg, 22%protein), P2R2 (restriction feed 20% of adlibitum, EM 2,800 kcal/kg, 23% protein), P0R1Cr (adlibitum feed, EM 2,900 kcal/kg, 22% protein with adding 2 ppm chromium), P0R2Cr (adlibitum feed, EM 2,800 kcal/kg, 23% with adding protein 2 ppm chromium), P1R1Cr (restriction feed 10% of adlibitum, EM 2,900 kcal/kg, 22% protein with adding 2 ppm chromium), P1R2Cr (restriction feed 10% from adlibitum, EM 2,800 kcal/kg, 23% protein with adding 2 ppm chromium), P2R1Cr (20% restriction feed of adlibitum, EM 2,900 kcal/kg, 22% protein with adding 2 ppm chromium) and P2R2Cr (restriction feed 20% from adlibitum, EM 2,800 kcal/kg, 23% protein with adding 2 ppm chromium). Parameters observed included feed intake, body weight gain, and feed conversion. The results showed that the addition of organic chromium to the limiting feed had a significant effect (P<0.01) on feed consumption, body weight gain, and feed conversion. Organic chromium might give 2 ppm on feed that was limited to 10% of EM 2,900 kcal/kg adlibitum, 22% protein.